ASSESSMENT OF SEASONAL PHYSICO-CHEMICAL PARAMETERS OF OGUTA LAKE, NIGERIA. - L.N, Ukiwe; Nwoko, C.I.A; Egereonu, U.U.; Ukachukwu, S.N. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Seasonal variation of physico-chemical variables of Oguta Lake, Nigeria was studied. Results obtained using standard analytical methods indicated that in the rainy and dry seasons (July and August) and (October and November), 2014, iron (Fe; 1.401 mg/l in November) was the overall metal observed in the lake, while mercury (Hg) was not detected throughout the period of study. Heavy metals concentrations observed were higher (not significantly) during the dry than the rainy season. The values observed for dissolved oxygen (DO), biological and chemical oxygen demand (BOD and COD) were within WHO permissible limits. The above evidence revealed that there was signs of heavy metal (Fe) pollution of the lake, and steps must be taking for constant monitoring of anthropogenic inputs into the lake.Â 